Feedback of the Medical Teachers Participated in Training Workshop on Assessment in Health Professions Education - Rano Mal Piryani; Nasir Ali Afsar; Suneel Piryani (Journal of Universal College of Medical Sciences, 2025)
INTRODUCTION Faculty development is a key component for smooth implementation of various curriculum strategies, including assessment in health professions education. A training workshop is one of the common faculty development programs to train teachers about tools and the process of assessment. Evaluating the training workshop is essential to know its impact. The objective of the study was to assess the feedback of participants at New World Kirkpatrick' Model (NWKM) level 1 & 2. MATERIAL & METHODS This was a cross-sectional study conducted in November 2022 at Bilawal Medical College, Liaquat University of Medical and Health Sciences to assess the participants’ feedback of Training Workshop on Assessment in Health Professions Education at NWKM level 1 & 2. A valid self-administered questionnaire was used for feedback. RESULTS The teaching and research experience of the participants (n= 17; Male 41%, Female 59%) were 5.12±4.63 years and 2.71±3.94. years respectively. The ratings of the participants overall as well as on the usefulness, content, relevance, and facilitation were remarkable. The significant positive change (p < 0.001) i.e. enhancement in the level of confidence of the participants in developing Multiple Choice Questions (MCQs); doing their item analysis; developing Objective Structured Clinical Examination (OSCE)/ Objective Structured Practical Examination (OSPE); developing Task Oriented Assessment of Clinical Skills (TOACS); and about screening research proposal was revealed by the participants. CONCLUSION Based on the immediate feedback of participants at NWKM level 1 & 2, this training workshop was successful in educating health professions education teachers about the common assessment tools of knowledge, skills and attitude.